Passively mode-locked fibre laser with semiconductor saturable absorption mirror - Lim, Jing Min. (2011)
An optical fiber has made tremendous advancements in the technology of mankind, made out of glass or plastic, the optical fiber is being produced cheaply due to the abundance of raw materials available. Besides being low cost, the other advantages include flexibility and lightweight.